2023
DOI: 10.3390/ijerph20065065
|View full text |Cite
|
Sign up to set email alerts
|

Vitality Revisited: The Evolving Concept of Flourishing and Its Relevance to Personal and Public Health

Abstract: Human flourishing, the state of optimal functioning and well-being across all aspects of an individual’s life, has been a topic of philosophical and theological discussion for centuries. In the mid-20th century, social psychologists and health scientists began exploring the concept of flourishing in the context of health and high-level wellness. However, it is only in recent years, in part due to the USD 43 million Global Flourishing Study including 22 countries that flourishing has entered the mainstream disc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 150 publications
1
8
0
Order By: Relevance
“…Our study uncovered a positive correlation between well‐being and the level of flourishing, which is in line with the findings of Gostin et al. (2023), who established well‐being as a reliable predictor of future health. Moreover, Lebares et al.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Our study uncovered a positive correlation between well‐being and the level of flourishing, which is in line with the findings of Gostin et al. (2023), who established well‐being as a reliable predictor of future health. Moreover, Lebares et al.…”
Section: Discussionsupporting
confidence: 93%
“…Well‐being and flourishing, which are often used interchangeably, refer to an optimal state of functioning across all aspects of life (Gostin et al., 2023). The PERMA™ theory developed by Martin Seligman identifies positive emotions, engagement, relationships, meaning, and accomplishment as the fundamental elements for flourishing (Seligman, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…The vital sign of vitality, or ‘inner aliveness’ (p. 64), for example, involves ‘help[ing] patients find their curiosity, enthusiasm, and passion’ (p. 63), and Logan et al. (2023) suggested that vitality is a largely neglected dimension of flourishing, or overall psychological wellness. Dual‐factor treatment models have evolved to promote flourishing (Jankowski, Captari, & Sandage, 2021); however, the effectiveness of psychotherapy to promote gains in flourishing remains largely empirically unanswered (Jankowski et al., 2020).…”
Section: Discussionmentioning
confidence: 99%
“…vision to promote a richer and more fulfilling life to be a worthwhile treatment goal, and McWilliams (2021) described vital signs of progress in psychodynamic psychotherapy 'that go beyond symptom reduction and that are basic to overall psychological wellness' (p. 67). The vital sign of vitality, or 'inner aliveness' (p. 64), for example, involves 'help[ing] patients find their curiosity, enthusiasm, and passion' (p. 63), andLogan et al (2023) suggested that vitality is a largely neglected dimension of flourishing, or overall psychological wellness. Dual-factor treatment models have evolved to promote flourishing(Jankowski, Captari, & Sandage, 2021);…”
mentioning
confidence: 99%
“…It does this by helping people capitalize on their strengths, heighten their gratitude and awareness, connect to others and develop the wisdom needed to live a more meaningful and fulfilling life. [49][50][51] According to Martin Seligman, exponent of positive psychology, "psychological well-being has been defined in various ways and encompasses the positive thoughts and feelings that individuals use to evaluate their lives favorably", suggesting that "individual-level interventions, such as mindfulness-based programs and positive psychological interventions, have shown promise for modifying psychological well-being". 52 In considering the protective role of positive psychological well-being in the evolution of health disorders, the most robust evidence comes from cardiovascular diseases, which is the leading cause of death worldwide and includes diagnoses such as coronary heart disease and stroke.…”
Section: Subjective Well-being In Other Fields: Positive Psychology A...mentioning
confidence: 99%